Wastes exist in library services - Choo, Han Yau; Lee, En Shin; Lok, Yee Peng; Ng, Shi Hui; Mohd Razali, Nurul Aimi Saleha; Ahmad, Azhar (2017)
Lean is a philosophy that deals with the waste that exists in between the customers and service providers.Due to its importance, it is highly critical that the study on this field at UUM library is conducted. Referring to the study, this article reflects critical outcomes in view of the following objectives, which are: (1) to identify the agreement level of waste in UUM library and (2) to analyze the issues regarding waste existed in library comparing across all the demographic factors.This study proceeded with the quantitative approach via a survey on 120 of UUM students.The results from the survey that analyzed by SPSS had showed significant differences on the student’ perception in view of the variable involved in the study.